Educating the Women of Hainan : The Career of Margaret Moninger in China, 1915-1942 - Lodwick, Kathleen L. (Book collections on Project MUSE., 1995)
For Margaret Moninger - a brilliant, fun-loving, and dedicated young woman from Iowa - a career as a missionary in China promised adventure and the chance for responsibility and authority denied most American women of her time. In 1915 she went as a Presbyterian missionary to Hainan Island, China's southernmost territory, where she remained until repatriated in 1942. Kathleen Lodwick's biography, the first devoted to a single woman missionary, is based primarily on the long, newsy letters Moninger wrote her family every Sunday of her missionary years, and on those of a fellow missionary. It will be of interest to scholars in Asian Studies, religious studies, and anthropology.